Tekanan Anggaran Waktu, Locus of Control, Kinerja dan Niat Mengundurkan Diri: Perilaku Audit disfungsional - Fatia Putri Rindawan (Jurnal Ekonomi Modernisasi, 2018)
This research aims to examine and to provide empirical evidence on the influence of time budget pressure, locus of control, performance and turnover intention to dysfunctional audit behavior. The dysfunctional audit behavior examined are audit quality reduction behavior (AQR) and underreporting of time (URT) behavior. This research uses survey method by using questionnaire to collect the data. The sample of this research is the auditor who work in Public Accounting Firm in East Java and are chosen by using purposive sampling technique. The data analysis uses Partial Least Square. The findings of this study prove that time budget pressure has a positive effect on dysfunctional audit behavior, locus of control has a positive effect on dysfunctional audit behavior, there is no negative effect of performance on dysfunctional audit behavior and there is positive influence of turnover intention to dysfunctional audit behavior. The finding of this study contributes to the development of accounting theory on behaviorism that is the attribution theory which states that the source of auditor behavior can be derived from internal factors and external factors. The results of this study can also be used as a reference for future researchers in the related field.